PENINGKATAN KINERJA GURU MELALUI SUPERVISI AKADEMIK KEPALA SEKOLAH DENGAN PENDEKATAN INDIVIDUAL DI SMA NEGERI 1 MAUMERE - JOHANES JONAS TETA, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The low learning outcomes of students in SMA Negeri 1 Maumere because students have not reached the mastery of learning that has been set (KKM). In addition, many students do not understand what is conveyed by the teacher due to lack of management and learning that is still teacher-centered. These problems are expected to be overcome through mentoring to teachers through supervision carried out by the principal with an individual approach from planning, implementing teaching and learning processes, to evaluating. The purpose of this study is an increase in teacher performance which will have implications for an increase in student learning outcomes. This research is through action research conducted in two cycles. Based on the results of the action research above, it can be concluded that the academic supervision of school principals with an individual approach gives an influence on improving the performance of teachers of Maumere 1 High School in terms of learning planning, learning implementation and evaluation components.